High-pervious concrete admixture and pervious concrete

By using highly permeable concrete admixtures, including modified polypropylene fibers and reinforced fillers, the problems of insufficient hardening and impermeable properties of permeable concrete are solved, and the improvement of high permeability and compressive strength is achieved, and the use is extended. Lifespan, suitable for sponge city construction.

CN119241129AActive Publication Date: 2025-01-03CHONGQING WULONG DISTRICT TRAFFIC ENGINEERING CO LTD

Patent Information

Application Number
CN202411419215.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

After construction, permeable concrete has hardened, poor fluidity, low flexural strength, poor toughness and low permeability, resulting in a shortened service life and insufficient permeability, making it difficult to meet the needs of sponge urban construction.

Method used

Using highly permeable concrete admixtures, including acrylic resin, modified polypropylene fibers, reinforced fillers and water reducers, the Elosite nanotubes and sodium alginate are modified to form a mesh structure and a hydrophobic membrane to improve the concrete's resistance. Pressure strength, impermeability and water permeability.

Benefits of technology

It significantly improves the compressive strength, permeability and water permeability of permeable concrete, extends its service life, and enhances the toughness and stability of concrete, and is suitable for sponge urban construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080287220000111
    Figure BDA0005080287220000111
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a high-pervious concrete admixture and pervious concrete. The pervious concrete admixture is prepared from the following raw materials in parts by weight: 25 to 35 parts of acrylic resin, 5 to 10 parts of modified polypropylene fiber, 15 to 25 parts of water reducing agent, 7 to 10 parts of kaolin and 15 to 25 parts of reinforcing filler, acrylic resin is used as an adhesive structure, and a functional additive is added to improve the compression resistance, the impermeability and the water permeability of the pervious concrete; wherein due to the introduction of the reinforcing filler, the compressive strength and the impermeability of the matrix are improved, and the water permeability, the pressure resistance and the impermeability of the matrix can be improved through the synergistic effect of the modified polypropylene fibers and the reinforcing filler, so that the service life of the pervious concrete is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a highly permeable concrete admixture and permeable concrete. Background Art

[0002] Permeable concrete is an important component of sponge city construction, which aims to improve urban water resource management, environmental quality and urban sustainability. Concrete itself has large pores, which allow water to enter the concrete from the upper surface and then flow out from the lower surface. The laying of permeable concrete pavement in the city has the following advantages: it can effectively replenish groundwater, alleviate flood disasters, provide a good travel environment and alleviate the heat island effect. However, permeable concrete hardens quickly during construction, has poor fluidity, low flexural strength, poor toughness, low water permeability and poor impermeability. In addition, the effects of rainwater scouring and cellar constraints during later use cause stress accumulation inside the permeable concrete, and the pores penetrate and expand each other, ultimately reducing the service life.

[0003] Among these problems, the poor toughness of permeable concrete itself is the most important. On the premise of ensuring that permeable concrete has excellent permeability, it is very necessary to conduct research dedicated to improving the strength and toughness of permeable concrete. Therefore, admixtures can be added to improve the compressive strength, water permeability coefficient, impermeability, antifreeze performance and other properties of permeable concrete, and ultimately increase the service life of permeable concrete. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a highly permeable concrete admixture and permeable concrete.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A highly permeable concrete admixture, comprising the following raw materials in parts by weight: 25-35 parts of acrylic resin, 5-10 parts of modified polypropylene fiber, 15-25 parts of water reducing agent, 7-10 parts of kaolin, and 15-25 parts of reinforcing filler;

[0007] The water reducing agent is prepared by mixing sodium tri(1-methylethyl)naphthalenesulfonate and sodium 2,6-di-tert-butylnaphthalenesulfonate in a mass ratio of 1:1-3;

[0008] The reinforcing filler is prepared by the following steps:

[0009] Step A1, dispersing vinyltrimethoxysilane in an ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 8-9, adding halloysite nanotubes, ultrasonicating for 10-20 minutes, stirring for reaction for 2-3 hours, centrifuging, washing, and drying to obtain surface-treated halloysite;

[0010] Step A2, mixing the surface treated halloysite, chloroplatinic acid isopropanol solution and toluene evenly, replacing with nitrogen three times, slowly adding hydrogen-containing silicone oil under nitrogen, heating to 80-90° C. for reaction for 1.5-2.5 h, distilling under reduced pressure, washing and drying to obtain a reinforcing filler;

[0011] Further, in step A1, the usage ratio of vinyltrimethoxysilane, ethanol solution, and halloysite nanotubes is 0.4-1 g: 20 mL: 1-3 g;

[0012] Furthermore, in step A2, the usage ratio of surface-treated halloysite, chloroplatinic acid isopropanol solution, toluene and hydrogenated silicone oil is 1-3 g: 5-10 g: 50 mL: 0.5-2 g, and the mass ratio of chloroplatinic acid and isopropanol in the chloroplatinic acid isopropanol solution is 0.05-0.1:100.

[0013] The modified polypropylene fiber is prepared by the following steps:

[0014] Step B1, dispersing morpholineethanesulfonic acid monohydrate in deionized water, adjusting the pH to 6, and then adding 0.3 mol / L sodium chloride solution to mix evenly, which is recorded as a buffer solution; dispersing sodium alginate in the buffer solution, adding EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) in sequence and stirring for 15 minutes, then adding allylamine hydrochloride (AH) to react for 12-24 hours, then adding ethanol and stirring, filtering and drying, and then re-dispersing the product in deionized water at a concentration of 1% (w / v), dialyzing for 2 days, and freeze-drying to obtain AH-sodium alginate;

[0015] Step B2, dispersing trimethylolpropane triglycidyl ether and tetrabutylammonium bromide in N,N-dimethylformamide, adding AH-sodium alginate, reacting for 1-2h under nitrogen and 80-90°C, adding tetrahydrofuran and stirring for 15min, filtering, washing and drying to obtain modified sodium alginate;

[0016] Step B3, the polypropylene and polyvinyl pyrrolidone are uniformly mixed, and then extruded through a twin-screw extruder, granulated, dried, melt-spun, and polypropylene fibers are collected. The polypropylene fibers are washed with anhydrous ethanol at a bath ratio of 1:10, and then washed with water at 60-80° C. for 1-2 hours and dried to obtain pre-treated polypropylene fibers;

[0017] Step B4, acetone, modified sodium alginate and benzophenone are stirred and mixed, added to the pre-treated polypropylene fiber and impregnated for 8-14 hours, and then irradiated under 320nm ultraviolet light for 2-3 hours, the product is collected, washed and dried to obtain modified polypropylene fiber;

[0018] Further, in step B1, the usage ratio of sodium alginate, buffer, EDC, NHS, allylamine hydrochloride and ethanol is 1 g: 100 mL: 0.02 mol: 0.01 mol: 0.005-0.02 mol: 200 mL;

[0019] Further, in step B1, the amount ratio of morpholineethanesulfonic acid monohydrate, deionized water and sodium chloride solution in the buffer solution is 0.01 mol: 90 mL: 10 mL;

[0020] Further, in step B2, the dosage ratio of trimethylolpropane triglycidyl ether, tetrabutylammonium bromide, N,N-dimethylformamide, AH-sodium alginate and tetrahydrofuran is 0.01-0.02 mol: 0.0005-0.0015 mol: 100 mL: 1-3 g: 100 mL;

[0021] Further, in step B3, the molar ratio of polypropylene to polyvinyl pyrrolidone is 5-10:0.5-2;

[0022] Furthermore, in step B4, the mass ratio of acetone, modified sodium alginate, benzophenone and pre-treated polypropylene fiber is 50:2-5:0.5-2:5-12.

[0023] In a second aspect, the present invention further provides a permeable concrete made of the highly permeable concrete admixture, which is prepared from the following raw materials in parts by weight: 30-60 parts of cement, 80-120 parts of gravel, 8-16 parts of highly permeable concrete admixture, and 15-25 parts of water;

[0024] Furthermore, the cement is P.O42.5 ordinary Portland cement.

[0025] Beneficial effects of the present invention:

[0026] The permeable concrete admixture of the present invention uses acrylic resin as an adhesive structure, and adds functional additives to improve the compressive strength, impermeability and water permeability of the permeable concrete; wherein the introduction of reinforcing fillers improves the compressive strength and impermeability of the matrix, and the modified polypropylene fiber can synergistically act with the reinforcing fillers to improve the water permeability, compressive resistance and impermeability of the matrix, thereby improving the service life of the permeable concrete.

[0027] In the reinforcing filler, the halloysite nanotubes are first modified with a coupling agent so that the surface contains a double bond structure, and then the double bond structure on the surface is used to react with the active hydrogen in the hydrogen-containing silicone oil to obtain the reinforcing filler. The introduction of reinforcing fillers can significantly improve the compressive strength and impermeability of permeable concrete. This is because the halloysite nanotubes have excellent mechanical properties and can work together with modified polypropylene fibers to coordinate the deformation of the matrix, thereby enhancing the toughness of the concrete and inhibiting the expansion of cracks. The network structure formed by the two in the cement base makes the concrete have a crack-resistant effect; at the same time, the presence of silicone oil also improves the impermeability of the matrix. This is because the hydrophobic silicone oil forms a hydrophobic film on the surface of the bonding layer that wraps the stone, allowing water to quickly pass through the pores without penetrating into the concrete, improving the impermeability of the concrete and thus increasing its service life.

[0028] In the modified polypropylene fiber, the amino group in allylamine is firstly reacted with sodium alginate activated by EDC and NHS to obtain AH-sodium alginate containing a double bond structure; then the epoxy group in trimethylolpropane triglycidyl ether is reacted with the hydroxyl group in AH-sodium alginate to obtain modified sodium alginate containing double bonds and epoxy structures; then a water-soluble polymer is mixed with polypropylene and spun to obtain polypropylene fiber, which is then washed with high temperature water to obtain pre-treated polypropylene fiber; finally, the modified sodium alginate is grafted onto the pre-treated polypropylene fiber by ultraviolet irradiation to obtain modified polypropylene fiber. The introduction of modified polypropylene fiber can improve the crack resistance, impermeability and water permeability of permeable concrete; among them, the water-soluble polymer in the pre-treated polypropylene fiber is dissolved by high-temperature water washing, so that the fiber forms a porous structure, changes the smooth surface characteristics of the fiber, and makes the fiber surface rough. The bonding effect between the rough surface and the cement base can increase the toughness of the concrete, improve the crack resistance and impermeability of the concrete, and at the same time, the porous structure can also improve the water permeability of the concrete; the epoxy group contained can undergo cross-linking, curing and filling with cement hydrates, thereby improving the stability and compressive resistance of the permeable concrete structure; in addition, the large number of hydrophilic groups contained in sodium alginate, such as carboxyl and hydroxyl, have certain water absorption properties, which improves the water permeability of the concrete. At the same time, the adhesion of sodium alginate enhances the friction between the internal particles of the concrete, thereby improving the strength of the concrete, and further enhancing the durability and service life of the permeable concrete. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] The reinforcing filler is prepared by the following steps:

[0032] Step A1, dispersing 0.4 g of vinyltrimethoxysilane in 20 mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 8, adding 1 g of halloysite nanotubes, ultrasonicating for 10 min, stirring for reaction for 2 h, centrifuging, washing, and drying to obtain surface-treated halloysite;

[0033] Step A2, 1g of surface-treated halloysite, 5g of chloroplatinic acid isopropanol solution and 50mL of toluene are mixed evenly, replaced with nitrogen three times, 0.5g of hydrogen-containing silicone oil is slowly added under nitrogen conditions, and the temperature is raised to 80°C for reaction for 1.5h, and distilled under reduced pressure, washed and dried to obtain a reinforced filler. The mass ratio of chloroplatinic acid and isopropanol in the chloroplatinic acid isopropanol solution is 0.05:100.

[0034] Modified polypropylene fiber is prepared by the following steps:

[0035] Step B1, dispersing 0.01 mol of morpholineethanesulfonic acid monohydrate in 90 mL of deionized water, adjusting the pH to 6, and then adding 10 mL of 0.3 mol / L sodium chloride solution to mix evenly, which is recorded as a buffer solution; dispersing 1 g of sodium alginate in 100 mL of buffer solution, adding 0.02 mol of EDC and 0.01 mol of NHS in sequence and stirring for 15 min, then adding 0.005 mol of allylamine hydrochloride (AH) to react for 12 h, then adding 200 mL of ethanol and stirring, filtering, drying, and then re-dispersing the product in deionized water at a concentration of 1% (w / v), dialyzing for 2 days, and freeze-drying to obtain AH-sodium alginate;

[0036] Step B2, 0.01 mol of trimethylolpropane triglycidyl ether and 0.0005 mol of tetrabutylammonium bromide were dispersed in 100 mL of N,N-dimethylformamide, and then 1 g of AH-sodium alginate was added, and the mixture was reacted under nitrogen at 80° C. for 1 h, and 100 mL of tetrahydrofuran was added and stirred for 15 min, and then filtered, washed and dried to obtain modified sodium alginate;

[0037] Step B3, 5 mol of polypropylene and 0.5 mol of polyvinyl pyrrolidone are uniformly mixed, and then extruded, granulated, dried, melt-spun, and polypropylene fibers are collected, and the polypropylene fibers are washed with anhydrous ethanol at a bath ratio of 1:10, and then washed with water at 60° C. for 1 hour, and dried to obtain pre-treated polypropylene fibers;

[0038] Step B4, stir and mix 50g of acetone, 2g of modified sodium alginate and 0.5g of benzophenone, add 5g of pretreated polypropylene fiber and soak for 8h, then irradiate under 320nm ultraviolet light for 2h, collect the product, wash and dry to obtain modified polypropylene fiber.

[0039] Example 2

[0040] The reinforcing filler is prepared by the following steps:

[0041] Step A1, dispersing 0.7 g of vinyltrimethoxysilane in 20 mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 8.5, adding 2 g of halloysite nanotubes, ultrasonicating for 15 min, stirring for reaction for 2.5 h, centrifuging, washing, and drying to obtain surface-treated halloysite;

[0042] Step A2, 2g of surface-treated halloysite, 7g of chloroplatinic acid isopropanol solution and 50mL of toluene are mixed evenly, replaced with nitrogen three times, 1g of hydrogen-containing silicone oil is slowly added under nitrogen conditions, and the temperature is raised to 85°C for reaction for 2h, and vacuum distilled, washed and dried to obtain a reinforced filler. The mass ratio of chloroplatinic acid and isopropanol in the chloroplatinic acid isopropanol solution is 0.07:100.

[0043] Modified polypropylene fiber is prepared by the following steps:

[0044] Step B1, dispersing 0.01 mol of morpholineethanesulfonic acid monohydrate in 90 mL of deionized water, adjusting the pH to 6, and then adding 10 mL of 0.3 mol / L sodium chloride solution to mix evenly, which is recorded as a buffer solution; dispersing 1 g of sodium alginate in 100 mL of a buffer solution, adding 0.02 mol of EDC and 0.01 mol of NHS in sequence and stirring for 15 min, then adding 0.01 mol of allylamine hydrochloride (AH) and reacting for 18 h, then adding 200 mL of ethanol and stirring, filtering, drying, and then re-dispersing the product in deionized water at a concentration of 1% (w / v), dialyzing for 2 days, and freeze-drying to obtain AH-sodium alginate;

[0045] Step B2, 0.015 mol of trimethylolpropane triglycidyl ether and 0.001 mol of tetrabutylammonium bromide were dispersed in 100 mL of N,N-dimethylformamide, and then 2 g of AH-sodium alginate was added, and the mixture was reacted under nitrogen at 85° C. for 1.5 h, 100 mL of tetrahydrofuran was added, and stirred for 15 min, and then filtered, washed, and dried to obtain modified sodium alginate;

[0046] Step B3, 7 mol of polypropylene and 1 mol of polyvinyl pyrrolidone are uniformly mixed, and then extruded through a twin-screw extruder, granulated, dried, melt-spun, and polypropylene fibers are collected. The polypropylene fibers are washed with anhydrous ethanol at a bath ratio of 1:10, and then washed with water at 70° C. for 1.5 h, and dried to obtain pre-treated polypropylene fibers;

[0047] Step B4, stir and mix 50g acetone, 3.5g modified sodium alginate and 1g benzophenone, add 9g pretreated polypropylene fiber and soak for 11h, then irradiate under 320nm ultraviolet light for 2.5h, collect the product, wash and dry to obtain modified polypropylene fiber.

[0048] Example 3

[0049] The reinforcing filler is prepared by the following steps:

[0050] Step A1, dispersing 1 g of vinyltrimethoxysilane in 20 mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 9, adding 3 g of halloysite nanotubes, ultrasonicating for 20 min, stirring for 3 h, centrifuging, washing, and drying to obtain surface-treated halloysite;

[0051] Step A2, 3g of surface-treated halloysite, 10g of chloroplatinic acid isopropanol solution and 50mL of toluene are mixed evenly, replaced with nitrogen three times, 2g of hydrogen-containing silicone oil is slowly added under nitrogen conditions, and the temperature is raised to 90°C for reaction for 2.5h, and distilled under reduced pressure, washed and dried to obtain a reinforced filler. The mass ratio of chloroplatinic acid and isopropanol in the chloroplatinic acid isopropanol solution is 0.1:100.

[0052] Modified polypropylene fiber is prepared by the following steps:

[0053] Step B1, dispersing 0.01 mol of morpholineethanesulfonic acid monohydrate in 90 mL of deionized water, adjusting the pH to 6, and then adding 10 mL of 0.3 mol / L sodium chloride solution to mix evenly, which is recorded as a buffer solution; dispersing 1 g of sodium alginate in 100 mL of a buffer solution, adding 0.02 mol of EDC and 0.01 mol of NHS in sequence and stirring for 15 min, then adding 0.02 mol of allylamine hydrochloride (AH) and reacting for 24 h, then adding 200 mL of ethanol and stirring, filtering, drying, and then re-dispersing the product in deionized water at a concentration of 1% (w / v), dialyzing for 2 days, and freeze-drying to obtain AH-sodium alginate;

[0054] Step B2, 0.02 mol of trimethylolpropane triglycidyl ether and 0.0015 mol of tetrabutylammonium bromide were dispersed in 100 mL of N,N-dimethylformamide, and 3 g of AH-sodium alginate was added, and the mixture was reacted under nitrogen at 90° C. for 2 h, and 100 mL of tetrahydrofuran was added and stirred for 15 min, and the mixture was filtered, washed and dried to obtain modified sodium alginate;

[0055] Step B3, 10 mol of polypropylene and 2 mol of polyvinyl pyrrolidone are uniformly mixed, and then extruded through a twin-screw extruder, granulated, dried, melt-spun, and polypropylene fibers are collected. The polypropylene fibers are washed with anhydrous ethanol at a bath ratio of 1:10, and then washed with water at 80° C. for 2 h, and dried to obtain pre-treated polypropylene fibers;

[0056] Step B4, stir and mix 50g acetone, 5g modified sodium alginate and 2g benzophenone, add 12g pretreated polypropylene fiber and soak for 14h, then irradiate under 320nm ultraviolet light for 3h, collect the product, wash and dry to obtain modified polypropylene fiber.

[0057] Example 4

[0058] The preparation of a highly permeable concrete admixture comprises the following steps:

[0059] Step S1, firstly, sodium tri(1-methylethyl)naphthalenesulfonate and sodium 2,6-di-tert-butylnaphthalenesulfonate are mixed in a mass ratio of 1:1 to prepare a water reducing agent;

[0060] Step S2, weigh the raw materials again by weight, mix and stir evenly 25 parts of acrylic resin, 5 parts of modified polypropylene fiber prepared in Example 1, 15 parts of water reducing agent, 7 parts of kaolin and 15 parts of reinforcing filler prepared in Example 1 to obtain a highly permeable concrete admixture.

[0061] Preparation of a permeable concrete: weigh the raw materials by weight, add 30 parts of P.O42.5 ordinary Portland cement, 80 parts of gravel, 8 parts of highly permeable concrete admixture prepared by the above method and 15 parts of water into a mixer, stir and mix evenly to obtain the concrete.

[0062] Example 5

[0063] The preparation of a highly permeable concrete admixture comprises the following steps:

[0064] Step S1, firstly, tri(1-methylethyl)naphthalene sodium sulfonate and 2,6-di-tert-butylnaphthalene sodium sulfonate are mixed in a mass ratio of 1:2 to prepare a water reducing agent;

[0065] Step S2, weigh the raw materials again by weight, mix and stir 30 parts of acrylic resin, 8 parts of modified polypropylene fiber prepared in Example 2, 20 parts of water reducer, 8 parts of kaolin and 20 parts of reinforcing filler prepared in Example 2 to obtain a highly permeable concrete admixture.

[0066] Preparation of permeable concrete: weigh the raw materials by weight, add 50 parts of P.O42.5 ordinary Portland cement, 100 parts of gravel, 12 parts of highly permeable concrete admixture prepared by the above method and 20 parts of water into a mixer, stir and mix evenly to obtain the permeable concrete.

[0067] Example 6

[0068] The preparation of a highly permeable concrete admixture comprises the following steps:

[0069] Step S1, firstly mix sodium tri(1-methylethyl)naphthalenesulfonate and sodium 2,6-di-tert-butylnaphthalenesulfonate in a mass ratio of 1:3 to prepare a water reducing agent;

[0070] Step S2, weigh the raw materials again by weight, mix and stir 35 parts of acrylic resin, 10 parts of modified polypropylene fiber prepared in Example 3, 25 parts of water reducing agent, 10 parts of kaolin and 25 parts of reinforcing filler prepared in Example 3 to obtain a highly permeable concrete admixture.

[0071] Preparation of a permeable concrete: weigh the raw materials by weight, add 60 parts of P.O42.5 ordinary Portland cement, 120 parts of gravel, 16 parts of highly permeable concrete admixture prepared by the above method and 25 parts of water into a mixer, stir and mix evenly to obtain the concrete.

[0072] Comparative Example 1

[0073] This comparative example provides a highly permeable concrete admixture and permeable concrete, which differs from Example 6 in that the reinforcing filler prepared in Example 3 is replaced by halloysite nanotubes, and the rest are the same.

[0074] Comparative Example 2

[0075] This comparative example is a highly permeable concrete admixture and permeable concrete, which differs from Example 6 in that polypropylene fiber is used instead of the modified polypropylene fiber prepared in Example 3, and the rest are the same.

[0076] The permeable concrete prepared in Examples 4-6 and Comparative Examples 1-2 was subjected to a performance test: After the raw material components were evenly mixed, several permeable concrete brick samples with a size of 20 cm×20 cm×5 cm were made, and the performance was tested after natural curing for 28 days;

[0077] Water permeability coefficient: refer to the water permeability coefficient test method disclosed in Appendix C of GB / T 25993-2010 "Permeable Pavement Bricks and Permeable Road Panels" for testing, and calculate the water permeability coefficient of different samples at a water temperature of 15°C;

[0078] Compressive strength: According to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the 28d compressive strength (MPa) of permeable concrete is tested;

[0079] Frost resistance: Tested with reference to the frost resistance test published in GB / T 4111-2013 "Test methods for concrete blocks and bricks";

[0080] The test results are shown in the following table:

[0081]

[0082] As can be seen from the above table, the highly permeable concrete admixture prepared by the present invention and the permeable concrete prepared by using the admixture have a water permeability coefficient within the range of 5.5 mm / s-6.0 mm / s, a 28d compressive strength within the range of 48.2 MPa-52.1 MPa, and an average compressive strength loss rate within the range of 0.93%-1.16%, indicating that the permeable concrete has the advantages of high permeability, excellent compressive resistance, excellent antifreeze performance, good impermeability and long service life, and has a wide range of applications.

[0083] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A highly permeable concrete admixture, characterized in that: A highly permeable concrete admixture, comprising the following raw materials in parts by weight: 25-35 parts of acrylic resin, 5-10 parts of modified polypropylene fiber, 15-25 parts of water reducing agent, 7-10 parts of kaolin, and 15-25 parts of reinforcing filler; The water reducing agent is prepared by mixing sodium tri(1-methylethyl)naphthalenesulfonate and sodium 2,6-di-tert-butylnaphthalenesulfonate in a mass ratio of 1:1-3; The reinforcing filler is prepared by the following steps: Step A1, dispersing vinyltrimethoxysilane in an ethanol solution, adjusting the pH to 8-9, adding halloysite nanotubes, ultrasonicating for 10-20 minutes, stirring for reaction for 2-3 hours, centrifuging, washing, and drying to obtain surface-treated halloysite; Step A2, the surface treated halloysite, chloroplatinic acid isopropanol solution and toluene are mixed evenly, nitrogen is replaced three times, hydrogen-containing silicone oil is slowly added under nitrogen conditions, and the temperature is raised to 80-90° C. to react for 1.5-2.5 hours, and vacuum distilled, washed and dried to obtain a reinforcing filler.

2. A highly permeable concrete admixture according to claim 1, characterized in that: In step A1, the usage ratio of vinyltrimethoxysilane, ethanol solution and halloysite nanotubes is 0.4-1 g: 20 mL: 1-3 g.

3. A highly permeable concrete admixture according to claim 1, characterized in that: In step A2, the usage ratio of surface-treated halloysite, chloroplatinic acid isopropanol solution, toluene and hydrogen-containing silicone oil is 1-3 g: 5-10 g: 50 mL: 0.5-2 g, and the mass ratio of chloroplatinic acid and isopropanol in the chloroplatinic acid isopropanol solution is 0.05-0.1:

100.

4. A highly permeable concrete admixture according to claim 1, characterized in that: The modified polypropylene fiber is prepared by the following steps: Step B1, dispersing morpholineethanesulfonic acid monohydrate in deionized water, adjusting the pH to 6, and then adding 0.3 mol / L sodium chloride solution to mix evenly, recorded as buffer; dispersing sodium alginate in the buffer, adding EDC and NHS in sequence and stirring for 15 minutes, then adding allylamine hydrochloride to react for 12-24 hours, then adding ethanol and stirring, filtering and drying, and then re-dispersing the product in deionized water at a concentration of 1 w / v%, dialyzing for 2 days, and freeze-drying to obtain AH-sodium alginate; Step B2, dispersing trimethylolpropane triglycidyl ether and tetrabutylammonium bromide in N,N-dimethylformamide, adding AH-sodium alginate, reacting for 1-2h under nitrogen and 80-90°C, adding tetrahydrofuran and stirring for 15min, filtering, washing and drying to obtain modified sodium alginate; Step B3, the polypropylene and polyvinyl pyrrolidone are uniformly mixed, and then extruded through a twin-screw extruder, granulated, dried, melt-spun, and polypropylene fibers are collected. The polypropylene fibers are washed with anhydrous ethanol at a bath ratio of 1:10, and then washed with water at 60-80° C. for 1-2 hours and dried to obtain pre-treated polypropylene fibers; Step B4, stir and mix acetone, modified sodium alginate and benzophenone, add pretreated polypropylene fiber and soak for 8-14 hours, then irradiate under 320nm ultraviolet light for 2-3 hours, collect the product, wash and dry to obtain modified polypropylene fiber.

5. A highly permeable concrete admixture according to claim 4, characterized in that: In step B1, the dosage ratio of sodium alginate, buffer solution, EDC, NHS, allylamine hydrochloride and ethanol is 1 g: 100 mL: 0.02 mol: 0.01 mol: 0.005-0.02 mol: 200 mL, and the dosage ratio of morpholineethanesulfonic acid monohydrate, deionized water and sodium chloride solution in the buffer solution is 0.01 mol: 90 mL: 10 mL.

6. A highly permeable concrete admixture according to claim 4, characterized in that: In step B2, the dosage ratio of trimethylolpropane triglycidyl ether, tetrabutylammonium bromide, N,N-dimethylformamide, AH-sodium alginate and tetrahydrofuran is 0.01-0.02 mol: 0.0005-0.0015 mol: 100 mL: 1-3 g: 100 mL.

7. A highly permeable concrete admixture according to claim 4, characterized in that: The molar ratio of polypropylene to polyvinyl pyrrolidone in step B3 is 5-10:0.5-2.

8. A highly permeable concrete admixture according to claim 4, characterized in that: In step B4, the mass ratio of acetone, modified sodium alginate, benzophenone and pre-treated polypropylene fiber is 50:2-5:0.5-2:5-12.

9. A permeable concrete made from the highly permeable concrete admixture according to any one of claims 1 to 8, characterized in that: The permeable concrete is prepared from the following raw materials in parts by weight: 30-60 parts of cement, 80-120 parts of gravel, 8-16 parts of highly permeable concrete admixture, and 15-25 parts of water.

10. The permeable concrete made from the highly permeable concrete admixture according to claim 9, characterized in that: The cement is P.O42.5 ordinary Portland cement.

Citation Information

Patent Citations

  • Ecological permeable concrete and preparing method thereof

    CN106187004A

  • Preparation method of pervious concrete admixture

    CN113087436A

  • Composition containing cellulose nanofibers and halloysite nanotubes, and film and composite containing the same

    JP2019094482A

  • Hybrid powder of halloysite nanotube-light scattering nanoparticle, method for preparing the same and cosmetic composition comprising the same for UV protection

    KR101116596B1

  • Polymeric composite including nanoparticle filler

    US20070106006A1

Cited By

  • Lubricating aluminum sheet with high heat dissipation performance and preparation method thereof

    CN119875453A